Alfabetização estética: o aluno do curso de pedagogia da UFC e as possibilidades da arte na sua formação como educador. - Paula, Daniele Facundo de (2010)
In this search, I investigated the art contribution to the educator’s upbringing. I intended to enlarge the comprehension of human formation influenced by the variety of art manifestations or throughout the aesthetic literacy process. In this perspective, I described the educational art conception in schools and academic fields and also. I pointed out the UFC teachers’ conception of the matter, focusing on the teachers from the Pedagogy Course of this institution. Then, throughout a confrontation process, I analyzed the expectations of the students from the Pedagogy Course of UFC in terms of the artistic literacy proposed by the art disciplines and their respective teachers and I also took into consideration the possibilities of meaning construction through the art. I described the field experience and the methodological path taken into an ethnographic research. I debated in which terms the cultural capital can be an important analytical element in the distribution of the cultural goods of the formal education and its repercussion as a social reproduction tool, having in mind that media is a relevant vehicle to socialize some of these cultural goods. Taking the experiences and discoveries of two students who had applied the non compulsory discipline Seminar II Art and Education in Schools, I highlighted the educators’ formation process in these disciplines. At last, I established a parallel between the investigated students’ experiences and the syllabus of the course. I hope in this search to contribute to strengthen the educators’ perception of the art relevance in their formation, mainly the importance of the disciplines which deals with the aesthetic dimension of the educators. Moreover, I wish to unleash in the mentioned course new debates concerning the rightness of aesthetic issue in education and its possibilities to achieve a human formation.